Development of fisheries and aquaculture in the context of Ukraine's european integration course - Didkovska Liudmyla; Дідковська Людмила; Didkovszka L. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2025)
Abstract. Aquatic bioresources are a valuable component of the population's nutrition and they play a significant role in ensuring global food security. Unlike global tendencies, Ukraine has experienced a persistent decline in fisheries and aquaculture production over the past decades (2000- 2022). The purpose of this study is to determine the impact of European integration on the Ukrainian fisheries and aquaculture sector and to summarise the key measures for effective fishing management in Ukraine. The methodological basis of this study included such methods of scientific cognition: monographic, dialectical, tabular, graphical, abstract and logical. Legislative and regulatory acts of Ukraine and the EU, scientific works of domestic and foreign scientists, as well as statistical indicators served as the primary sources of information during the research. The author used the data of the State Statistics Service of Ukraine, Ministry of Agrarian Policy and Food of Ukraine, EUROSTAT. The main factors that slow down the development of the Ukrainian fishing industry have been summarised: high level of moral and physical depreciation of fixed assets; sectoral shadowing due to the lack of proper control and accountability for not submitting reports; problems with the supply of fish planting materials; negative anthropogenic and climatic impacts on aquatic ecosystems etc. Including Ukraine's aspirations for European integration, it is essential to consider the potential consequences of EU accession for the Ukrainian fisheries and aquaculture. The primary expected advantages include: de-shadowing, improving the quality of fish products, increasing funding, expanding export potential, modernising of outdated equipment, and gaining access to innovative technologies and practices in fish extraction and processing. The dynamic of foreign trade of fish and crustaceans of Ukraine with EU countries shows that, despite the small share of fish and crustaceans in the overall commodity structure with EU countries, exports of these items had a positive growth trend before the full-scale war. However, in 2022 fish and crustaceans exports to EU countries have decreased by more than one and a half times,. To ensure effective management of the domestic fishing industry in the context of European integration, it is crucial to: bring the national legislation in line with the European one, including the implementation of more than 30 EU acts; digitalise and deregulate the industry, ensuring traceability of aquatic bioresources; implement sustainable fishing practices, including the development of organic aquaculture, etc.

A vízi biológiai erőforrások a lakosság táplálkozásának értékes összetevői, és jelentős szerepet játszanak a globális élelmezésbiztonság biztosításában. A globális tendenciákkal ellentétben Ukrajnában az elmúlt évtizedekben (2000-2022) a halászati és akvakultúra-termelés tartósan csökkent. E tanulmány célja, hogy meghatározza az európai integráció hatását az ukrán halászati és akvakultúra-ágazatra, és összefoglalja a hatékony halászati gazdálkodás kulcsfontosságú intézkedéseit Ukrajnában. A tanulmány módszertani alapját következő módszerek képezték: monografikus, dialektikus, táblázatos, grafikus, absztrakt és logikai. A kutatás során elsődleges információforrásként Ukrajna és az EU törvényi és rendeleti aktusai, hazai és külföldi tudósok tudományos munkái, valamint statisztikai mutatók szolgáltak. A szerző felhasználta az Ukrán Állami Statisztikai Szolgálat, Ukrajna Agrárpolitikai és Élelmezésügyi Minisztériuma, az EUROSTAT adatait. Az ukrán halászati ágazat fejlődését lassító fő tényezők a következők: az tárgyi eszközök magas szintű erkölcsi és fizikai értékcsökkenése; a megfelelő ellenőrzés hiánya miatti ágazati árnyékolás és a jelentések benyújtásának elmulasztása miatti elszámoltathatóság; a haltelepítési anyagok ellátásával kapcsolatos problémák; a vízi ökoszisztémákra gyakorolt negatív antropogén és éghajlati hatások stb. Ukrajna európai integrációs törekvéseit is figyelembe véve alapvető fontosságú, hogy megvizsgáljuk az EU-csatlakozás lehetséges következményeit az ukrán halászatra és akvakultúrára nézve. Az elsődleges várható előnyök a következők: árnyékmentesítés, a haltermékek minőségének javítása, a finanszírozás növelése, az exportlehetőségek bővítése, az elavult berendezések korszerűsítése, valamint a halak kitermelésével és feldolgozásával kapcsolatos innovatív technológiákhoz és gyakorlatokhoz való hozzáférés. Ukrajna és az EU országai közötti hal- és rákfélék külkereskedelmének dinamikája azt mutatja, hogy annak ellenére, hogy a halak és rákfélék részesedése az EU országaival folytatott teljes áruszerkezetben csekély, e termékek kivitele a teljes körű háború előtt pozitív növekedési tendenciát mutatott. Azonban 2022-ben az uniós országokba irányuló hal- és rákfélék kivitele több mint másfélszeresére csökkent,. A hazai halászati ágazat hatékony irányításának biztosítása érdekében az európai integráció összefüggésében elengedhetetlenül fontos: a nemzeti jogszabályok összhangba hozása az európai jogszabályokkal, beleértve a több mint 30 uniós jogszabály végrehajtását; az ágazat digitalizálása és deregulációja, a vízi biológiai erőforrások nyomon követhetőségének biztosítása; fenntartható halászati gyakorlatok bevezetése, beleértve az ökológiai akvakultúra fejlesztését stb.

Резюме. Водні біоресурси є цінним компонентом харчування населення та відіграють значну роль у забезпеченні глобальної продовольчої безпеки. На відміну від світових тенденцій, в Україні протягом останніх десятиліть (2000-2022 рр.) спостерігалося стійке зниження обсягів добування (вилову) у рибогосподарському секторі. Метою дослідження є визначення впливу європейської інтеграції на український сектор рибальства та аквакультури, а також узагальнення ключових заходів для ефективного управління рибним господарством України. Методологічною основою дослідження стали такі методи наукового пізнання: монографічний, діалектичний, табличний, графічний та абстрактно-логічний. Основними джерелами інформації під час дослідження були законодавчі та нормативні акти України та ЄС, наукові праці вітчизняних і зарубіжних учених, а також статистичні показники. Зокрема, використано дані Державної служби статистики України, Міністерства аграрної політики та продовольства України, а також EUROSTAT. У роботі узагальнено основні фактори, які гальмують розвиток української рибної галузі: високий рівень морального та фізичного зносу основних засобів; тінізація галузі через брак належного контролю та відповідальності за неподання звітності; проблеми з постачанням рибопосадкового матеріалу; негативний антропогенний та кліматичний вплив на водні екосистеми тощо. З огляду на прагнення України до європейської інтеграції, важливо враховувати потенційні наслідки вступу до ЄС для українського сектору рибальства та аквакультури. Зокрема, до основних очікуваних переваг слід віднести: детінізацію галузі, покращення якості рибної продукції, збільшення фінансування, розширення експортного потенціалу, модернізацію застарілого обладнання та доступ до інноваційних технологій і практик у сфері вилову та переробки риби. Динаміка зовнішньої торгівлі рибою та ракоподібними України з країнами ЄС свідчить, що, незважаючи на невелику частку цієї продукції в загальній товарній структурі з ЄС, експорт риби та ракоподібних демонстрував позитивну динаміку до початку повномасштабної війни. Однак у 2022 році експорт риби та ракоподібних до країн ЄС знизився більш ніж у півтора раза. Для забезпечення ефективного управління вітчизняною рибною галуззю в умовах європейської інтеграції необхідно: гармонізувати національне законодавство з європейським, включаючи впровадження понад 30 актів ЄС; цифровізувати та дерегулювати галузь, забезпечивши простежуваність водних біоресурсів; впровадити сталі практики рибальства, включаючи розвиток органічної аквакультури, тощо.
Розвиток рибальства та аквакультури в контексті євроінтеграційного курсу України
A halászat és az akvakultúra fejlesztése Ukrajna európai integrációs folyamatának összefüggésében
Редакційна колегія: https://aab-economics.kmf.uz.ua/aabe/about/editorialTeam
Зміст: https://aab-economics.kmf.uz.ua/aabe/issue/view/8
Keywords: fisheries; aquaculture; aquatic bioresources; food security; European integration